New non-SARA-based correlations for predicting asphaltene deposition - Sulaimon, A.A. (Society of Petroleum Engineers, 2020)
Asphaltene deposition constitutes a major flow assurance challenge during oil production. Several attempts have been made to predict asphaltene stability using SARA analysis, which is usually expensive and time-consuming. Therefore, we have developed new SARA-independent correlations for the colloidal instability index (CII) and the refractive index (RI) as functions of oil density. The new density-based CII or DBCII is proven to be reliable with an average absolute relative error (AARE) of 0.1428, standard deviation (SD) of 0.1902 and a correlation coefficient R2 of 0.9520. Similarly, density-based RI or DBRI has been validated with an AARE of 0.0037 and SD of 0.0044. Two new deposition envelops have been developed with different criteria. The stable regions are characterized by DBCII lesser than 1.1 and DBRI greater than 1.525 while the unstable zones are defined when DBCII is greater than 1.8 and DBRI lesser than 1.503. The metastable region is identified within the limits of stable and unstable criteria. Comparative analyses have shown that the new correlations are simpler, cheaper and more accurate than the existing SARA-fractions-dependent-RI correlation and molecular-weight-dependent CII correlation. Copyright Â© 2020 Society of Petroleum Engineers.